Origin of colossal permittivity and low dielectric loss in Na1/3Cd1/3Y1/3Cu3Ti4O12 ceramics. Issue 8 (1st June 2020) - Peng, Zhanhui; Zhou, Xiaobin; Wang, Jitong; Zhu, Jie; Liang, Pengfei; Chao, Xiaolian; Yang, Zupei
Abstract: We designed a new type of perovskite-related dielectric material Na1/3 Cd1/3 Y1/3 Cu3 Ti4 O12 (NCYCTO) with colossal permittivity via a solid-state method. A decent dielectric performance of colossal permittivity ~4.0 × 10 4 and low dielectric loss ~0.065 was achieved in NCYCTO ceramics sintered at 1060 °C for 15 h. Electronic heterogeneity structure in NCYCTO ceramics was confirmed combined with the analysis of the dielectric properties, conductivity characteristics and complex impedance behavior, which consist of semiconductor grains and large resistance insulating grain boundary. Notably, internal barrier layer capacitor effect was adopted to explain the decent dielectric performance based on the analysis of dielectric response behavior and complex impedance. Our finding in this work not only explored the dielectric response of the new type of giant dielectric ceramics Na1/3 Cd1/3 Y1/3 Cu3 Ti4 O12 but also provides useful insight to simultaneously realize the low dielectric loss and colossal permittivity in ACu3 Ti4 O12 dielectric ceramics. Graphical abstract: Image 1